USM TO INTRODUCE SPECIAL SCHEME TO RETAIN ACADEMIC TALENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 6 January 2017 The USM Registrar, Professor Dato' Dr. Abd Aziz Tajuddin has provided the details on the effort by Universiti Sains Malaysia (USM) to introduce a special scheme for retaining its academic talents who have retired to ensure that there is continuity in its knowledge circle.